The past, present and future of agriculture policy in Africa - Badiane, Ousmane; Collins, Julia; Ulimwengu, John M. (International Food Policy Research Institute, 2020)
This chapter reviews changes in Africa’s economic and agricultural development, and explores their origins in the types of policies pursued by leaders. It examines the strategies and economic trends of the past, in the decades since independence; discusses the innovations of the current Comprehensive Africa Agriculture Development Programme (CAADP) era; and describes future policy challenges as we approach the third decade of CAADP implementation. In the first section, we review trends over the past decades in economic growth, agricultural production and productivity, and poverty and hunger. Next, we describe the evolution of agricultural and macroeconomic policies in the decades since Africa’s independence. The third section uses econometric analysis to link policy changes and macroeconomic management indicators to economic growth outcomes. The fourth section describes policy renewal efforts under CAADP, and the next section discusses the growing danger of policy reversal and the importance of mutual accountability processes to mitigate this risk. The sixth section discusses new and emerging policy challenges facing policymakers today, and the final section concludes with some remarks on the way forward.